Blackfishing y otras formas de naturalización de las prácticas coloniales en el siglo XXI desde una mirada interseccional - Fariña, Milagros (2022)
"XIX Dr. Ignacio Winizky essay contest on "Legal approaches to racial discrimination". -- The marginalization and epistemic subjugation of racialized groups has its origin in a world-system governed by the Eurocentric norm of modern/ colonial forms of knowledge, which has brought about an invisibilization of the interconnection that exists between the multiple edges of discrimination in the globalized world. It is through the intersectionalization of decolonial feminism that we can elucidate the number of issues faced by racialized women and how they all respond to the same colonial and patriarchal logic implicit in many attitudes of whiteness that we reproduce consciously or unconsciously